Diurnal changes of the oral microbiome in patients with alcohol dependence - Li, Xiangxue; Zhao, Kangqing; Chen, Jie; Ni, Zhaojun; Yu, Zhoulong; Hu, Lingming; Qin, Ying; Zhao, Jingwen; Peng, Wenjuan; Lu, Lin; Gao, Xuejiao; Sun, Hongqiang (Frontiers in Cellular and Infection Microbiology, 2022)
Background：The saliva secretion and oral microbiota also changes in rhythm with our biological clock. Dysbiosis of the oral microbiome and alcohol consumption have a two-way interactive impact, but little is known about whether the oral microbiome has diurnal changes in composition and function during the daytime in patients with alcohol dependence (AD). Methods：The impact of alcohol consumption on the diurnal salivary microbiome was examined in a case control study of 32 AD patients and 21 health control (HC) subjects. We tested the changes in microbial composition and individual taxon abundance by 16S rRNA gene sequencing. Results：The present study is the first report showing that that alcohol consumption enhanced the richness of the salivary microbiome and lowered the evenness. The composition of the oral microbiota changed a lot in alcohol dependence patients. Additionally, certain genera were enriched in the AD group, including Actinomyces, Leptotrichia, Sphaerochaeta and Cyanobacteria, all of which have pathogenic effects on the host. There is a correlation between liver enzymes and oral microbiota. KEGG function analysis also showed obvious alterations during the daytime. Conclusion: Alcohol drinking influences the diurnal changes of the oral microbiota, leading to flora disturbance and related function impairment. In particular, the diurnal changes of the oral microbiota may open avenues for potential interventions that can relieve the detrimental consequences of AD.